Infrastructure and poverty reduction: Implications for urban development in Nigeria - T. P. Ogun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The paper investigates the impact of infrastructural development on poverty reduction in Nigeria. Specifically, the relative effects of physical and social infrastructure on living standards or poverty indicators are examined, with a view to providing empirical evidence on the implications of increased urban infrastructure for the urban poor. The paper employs secondary data for the period 1970:1 to 2005:4 and the structural vector autoregressive (SVAR) technique is adopted in the analysis. The study unequivocally finds that infrastructural development leads to poverty reduction. Results also show that though infrastructure in general reduces poverty, social infrastructure explains a higher proportion of the forecast error in poverty indicators relative to physical infrastructure. This suggests that massive investment in social infrastructure in cities would drastically reduce poverty in the urban areas.
Keywords: R0; O10; 330; African urbanism; everyday practices; social infrastructures; urban violence